Tinjauan Pengaruh Sistem Akuntansi Penggajian Dan Pengupahan Dalam Mendukung Pengendalian Intern Gaji Dan Upah Pada Hotel Salak The Heritage - Roestiono, Harry; Nurfithriyani, Siti; Marlin, Tarida (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
The roles of internal control and accounting information system owned by a firm cannot be separated with each other in company’s operating in order to run smoothly and in accordance with the standardised procedures. And so with payroll and payment operating, it takes a proper system to run its activities. Thus, the company will be able to avoid possible risks during transactions. This research is aimed at investigating how the application of payroll system and to determine if the existing system helps the management in controlling its payroll and payment system. This is a descriptive research using primary data such as interviews with management and secondary data. Data are collected using observation technique, interviews and library research. The result concludes that the company has run a proper system in its payroll and thus helped the management to control its payroll and payment system.